Assessment of the possibility of irradiating tungsten and Cu-alloys in IFMIF-DONES using a realistic specimens configuration - Irene Álvarez; Marta Anguiano; Fernando Mota; Rebeca Hernández; David Sosa; Fabio Moro; Simone Noce; Yuefeng Qiu; Jin Hun Park; Frederik Arbeiter; Iole Palermo (Nuclear Fusion)
IFMIF-DONES (International Fusion Materials Irradiation Facility-DEMO Oriented NEutron Source) is a facility whose purpose is to obtain data on materials by irradiating them under conditions equivalent to those of the DEMO (DEMOstration) fusion reactor. Tungsten and CuCrZr alloy are two candidate materials to be used in DEMO, tungsten for the first wall and divertor (DIV) and CuCrZr alloy for the DIV. So, studying the behavior of these materials in IFMIF-DONES facility and comparing the results with the DEMO environment is crucial. In the high flux test module in IFMIF-DONES has been considered a realistic distribution of specimens. The IFMIF-EVEDA beam have been used with a footprint size of 20 × 5 cm ^2 , the nominal energy is 40 MeV with a current of 125 mA, for the calculation other energies have been considered 25, 30 and 35 MeV. The results of IFMIF-DONES have been compared with different DEMO concepts, Dual Coolant Lithium Lead, Water Cooled Lithium Lead and Helium Cooled Pebble Bed. In general, the primary displacement damage rate meets between IFMIF-DONES and DEMO, while the gas production is at the limit for W and fulfilled for the CuCrZr alloy.